Development of a Remote Three-Phase Motor Wiring Practice Tool Using ESP32, LabVIEW, Wokwi, and Adafruit IO - Artanto, Dian; Cahyono, Eko Aris Budi; Arbiyanti, Pippie (Journal of Electronics Technology Exploration, 2024)
The practical application of three-phase induction motor wiring is an essential part of mechatronic engineering education. The integration of IoT-based tools and simulation software such as Wokwi, LabVIEW, and Adafruit IO enables remote monitoring and control of motor wiring practices. This article discusses the development of a remote three-phase induction motor wiring tool utilizing the ESP32 microcontroller, LabVIEW for real-time monitoring and control, Wokwi for circuit wiring simulation, and Adafruit IO for cloud-based data communication. Testing shows that the system effectively facilitates remote motor control and wiring simulation, providing a flexible and accessible learning environment.